Multifunctional medical dressing assisted by laser additive technology
Patent Information
- Application Number
- CN202521444079.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2035-07-10
AI Technical Summary
[0007]本实用新型的目的是克服现有医用敷料载药效率低、药物释放不可控、功能单一且力学性能易受损等不足,提供一种激光增材技术辅助的多功能医用敷贴,该医用敷贴以聚氨酯薄膜、无纺布、明胶海绵或水凝胶为基材,通过激光在基材表面精确构建出蜂窝状纳米银微腔室阵列,腔内负载由抗菌药物、促生长因子及止血药物复配的多功能复合体系
[0018]本实用新型的有益效果在于:本实用新型基于3D微纳米激光增材技术,在传统医用基材表面构建了具有密排结构的蜂窝状微腔室阵列,其内负载药物体系以及纳米银,同时发挥广谱抗菌、促进组织再生和抗凝止血的作用。通过水凝胶实现药物的控制释放,通过微腔室结构显著提升单位面积载药效率,支持临床场景定制化的多药物精准调配,同时也保留了基材的原始机械性能(断裂伸长率、机械强度、透湿性等)。本实用新型医用敷贴在急慢性创面护理领域具有广阔的应用前景与潜力,为临床难治性创面管理提供了解决方案。
Smart Images

Figure CN224864774U_ABST
Abstract
Description
Technical Field
[0001] This utility model belongs to the field of biomedical materials and wound care, and particularly relates to a multifunctional medical dressing assisted by laser additive manufacturing technology. Background Technology
[0002] With the increasing demands of healthcare, the global medical dressing market is undergoing a functional transformation from traditional passive coverage to active therapeutic functions. As the body's most important protective barrier, damage to the skin's integrity not only significantly increases the risk of local infection but can also trigger serious complications such as systemic inflammatory responses. Clinical data shows that chronic wound infections have become a significant medical problem affecting patients' quality of life, especially difficult-to-heal wounds such as diabetic foot ulcers, which have long treatment cycles and high costs, placing a heavy burden on the healthcare system.
[0003] Although international high-end antibacterial dressings have adopted advanced technologies such as nano-silver and hydrogels to improve performance, they still face core challenges such as uncontrollable drug release and high costs. For example, the cost of a single high-end medical dressing exceeds $30, and traditional drug delivery methods often lead to burst drug release, which cannot match the wound healing cycle. More importantly, existing drug delivery technologies often sacrifice material mechanical properties, severely limiting their application value in complex wounds. Market analysis shows that the global wound dressing market reached $13.7 billion in 2022, with high-end dressings accounting for more than 54%. However, this field has long been monopolized by international giants, while domestic companies mainly focus on the low-to-mid-end market.
[0004] In recent years, laser processing technology has offered new possibilities for dressing development. Domestic and international research teams have attempted to apply technologies such as photolithography and 3D printing to dressing preparation. For example, laser-induced graphene structures have enabled the customized fabrication of smart honeycomb structures, and the regulation rules for their multifunctional properties have been established. However, these technologies generally suffer from complex processes and reliance on imported equipment, making industrialization difficult. Furthermore, while research based on dressing substrates has developed various drug-loaded nanofiber dressings through technologies such as electrospinning, large-scale production still faces significant challenges. Despite my country's strong capabilities in laser processing, this disconnect between technology, industry, and clinical application severely restricts the development of my country's high-end dressing industry.
[0005] To address the aforementioned key issues, this invention proposes an innovative solution: a precision drug-carrying system constructed using laser additive manufacturing technology, combined with a multi-mechanism composite drug system, achieves a breakthrough upgrade in wound dressings. Technically, a honeycomb-like micro-chamber array is constructed on the surface of a medical substrate using laser processing, achieving a precision of up to 100nm. This not only significantly improves drug loading efficiency but also enables intelligent drug release through hydrogels. Regarding the drug system, relying on the drug delivery system, three classes of drugs—antibacterial, growth-promoting, and hemostatic—are innovatively integrated and personalized according to clinical needs, forming a comprehensive treatment and care for various types of wounds at different stages. This multi-mechanism synergistic design overcomes the limitations of single-drug approaches and achieves precise control of the wound microenvironment.
[0006] The development of this technology has significant clinical value and industrialization prospects. On the one hand, it can effectively solve the clinical challenges of long healing periods and low healing rates in acute and chronic wounds, especially offering unique advantages for refractory wounds such as diabetic foot ulcers. On the other hand, compared with similar international technologies, it will significantly reduce processing costs and, being entirely based on domestically produced equipment, possesses significant industrialization advantages. The application of this technology will not only fill the shortage in the domestic high-end dressing market but will also further promote the in-depth development of laser manufacturing technology in the biomedical field. Utility Model Content
[0007] The purpose of this invention is to overcome the shortcomings of existing medical dressings, such as low drug loading efficiency, uncontrollable drug release, single function, and easy damage to mechanical properties. This invention provides a multifunctional medical dressing assisted by laser additive manufacturing technology. The medical dressing uses polyurethane film, non-woven fabric, gelatin sponge, or hydrogel as the substrate. A honeycomb-shaped array of nano-silver microcavities is precisely constructed on the surface of the substrate by laser. The cavity is loaded with a multifunctional composite system composed of antibacterial drugs, growth factors, and hemostatic drugs.
[0008] To achieve the above objectives, this application adopts the following technical solution: This invention provides a multifunctional medical dressing assisted by laser additive manufacturing technology, including a medical dressing substrate and a nano-silver microcavity for loading drugs. The nano-silver microcavity is bonded to the medical dressing substrate. The nano-silver microcavity is made of nano-silver composite material by laser processing and has multiple microcavity units capable of containing the drugs.
[0009] In the above technical solutions, the micro-chamber units are arranged in a honeycomb array.
[0010] In the above technical solutions, the projected area of the micro-chamber unit is 100-2500μm², the depth is 100-5000nm, the cavity wall tilt angle is 70°-85°, and the density is 100-1000 units / mm².
[0011] In the above technical solutions, the medical dressing substrate includes one of polyurethane film, non-woven fabric, gelatin sponge and hydrogel.
[0012] In the above technical solutions, the microchamber unit is either hexagonal or square.
[0013] In the above technical solution, a connecting microchannel is provided between adjacent microchamber units, and the diameter of the connecting microchannel is 1-5μm.
[0014] In the above technical solution, the nano-silver composite material contains nano-silver particles with a particle size of 10-100nm, and its surface is modified with polyvinylpyrrolidone (PEG).
[0015] In the above technical solutions, the drug includes one or more of the following: antibacterial agents, growth factors, and hemostatic agents.
[0016] In the above technical solution, the drug is loaded in three layers within the microchamber monomer: the top layer is a hemostatic agent, the middle layer is an antibacterial agent, and the bottom layer is a growth factor.
[0017] In the above technical solution, the drug is loaded into the nano-silver microcavity by means of hydrogel filling.
[0018] The beneficial effects of this invention are as follows: Based on 3D micro-nano laser additive manufacturing technology, this invention constructs a honeycomb-like micro-chamber array with a densely packed structure on the surface of a traditional medical substrate. The array is loaded with a drug system and nano-silver, simultaneously exerting broad-spectrum antibacterial, tissue regeneration-promoting, and anticoagulant hemostatic effects. Controlled drug release is achieved through hydrogel, and the micro-chamber structure significantly improves drug loading efficiency per unit area, supporting customized multi-drug precise formulation for clinical scenarios. It also preserves the original mechanical properties of the substrate (elongation at break, mechanical strength, moisture permeability, etc.). This medical dressing has broad application prospects and potential in the field of acute and chronic wound care, providing a solution for the management of refractory wounds in clinical practice. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the structure of the medical dressing of this utility model.
[0020] Figure 2 This is a SEM microstructure of the honeycomb-shaped nano-silver microchamber array of this utility model and a single-chamber schematic diagram, wherein: (a) hexagonal and square closely packed microchambers under low magnification; (b) cross-sectional view of the medical dressing of this utility model and a single-chamber structure diagram; (c) distribution of nano-silver particles on the cavity wall (SEM image).
[0021] Figure 3This is a 3D fluorescence reconstruction image of the microcompartment drug delivery system of this invention. The three-dimensional distribution and pattern diagram of the drug-loaded microcompartments are presented through confocal microscopy, and the loading position of the fluorescently labeled antibacterial drug (green) is shown.
[0022] Figure 4 This is a diagram showing the experimental results of mechanical property testing of medical substrates after laser additive manufacturing.
[0023] Figure 5 This is a drug release kinetic curve of a multifunctional dressing.
[0024] Figure 6 This is a diagram from an in vitro antibacterial performance test.
[0025] Figure 7 These are images of wound healing effects in animal models, including: (a) a macroscopic image of the wound healing process in rats with contaminated wounds; and (b) tissue sections showing increased vascular density in the experimental group (microcavity drug-loaded) compared to the control group (conventional dressing) (HE staining).
[0026] Figure 8 This is an experimental diagram showing the results of a platelet adhesion test. It compares platelet adhesion in an in vitro whole blood contact experiment (microcompartment drug loading) with the control group (traditional dressing).
[0027] Among them: 1. Medical dressing substrate; 2. Nano-silver microcavity; 21. Microcavity unit; 22. Connecting microchannel; 3. Drug. Detailed Implementation
[0028] To better illustrate the purpose, technical solution, and advantages of this utility model, it will be further described below with reference to specific embodiments. This utility model can be implemented in many different forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the concept of this utility model to those skilled in the art, who will define this utility model only by the claims.
[0029] Acute and chronic wound infections are a major challenge in clinical treatment, often leading to prolonged wound healing and even endangering patients' lives. To address this problem, this invention uses traditional medical dressings as a substrate and employs laser etching instruments (including 3D micro-nano lasers and conventional laser additive manufacturing technology) to construct a honeycomb-shaped micro-chamber array on the substrate surface. This not only preserves the original moisture permeability and flexibility of the dressing but also achieves controlled drug release from the wound microenvironment.
[0030] Laser etching technology significantly enhances the drug loading capacity of the substrate. The nano-silver and composite drug system loaded in the microcavities can simultaneously exert a synergistic effect of broad-spectrum antibacterial activity, promoting tissue regeneration, and anticoagulation and hemostasis. This dressing can effectively prevent and treat wound infections and accelerate the healing process.
[0031] This utility model provides a multifunctional medical dressing assisted by laser additive technology, including a medical dressing substrate 1, a nano-silver micro-cavity 2 bonded to the medical dressing substrate 1, and a drug 3 loaded in the nano-silver micro-cavity 2. The nano-silver micro-cavity 2 is made of nano-silver composite material by laser processing and has multiple micro-cavity units 21 that can accommodate the drug 3.
[0032] In this invention, the medical dressing substrate 1 can be selected from commercially available traditional medical dressing substrates, such as polyurethane film, non-woven fabric, gelatin sponge, hydrogel, etc.
[0033] Both the medical dressing substrate 1 and the nano-silver microcavity 2 are hydrophilic, with a surface water contact angle of 30°-60°.
[0034] In this invention, the drug can be loaded into the nano-silver microcavity 2 in the following two ways: (1) The drug loaded in the microcavity is filled with pH-responsive polymer N-isopropylacrylamide hydrogel. The hydrogel is a covalent cross-linked network formed by photopolymerization of N-isopropylacrylamide, with a swelling ratio of 200%-500% and an elongation at break of ≥300%.
[0035] (2) The microcavities are directly adhered to the drug.
[0036] In this invention, the nano-silver composite material contains nano-silver particles with a particle size of 10-100 nm, and its surface is modified with polyvinylpyrrolidone (PEG) with a loading of 0.5-2 mg / cm².
[0037] In this invention, laser processing can be performed in the following two ways: (1) The 3D micro-nano laser etching process uses femtosecond lasers with wavelengths of 100-1000nm and pulse widths of 10-100fs, scanning speeds of 1-10mm / s, and power of 10-100mW.
[0038] (2) The conventional laser additive manufacturing process uses ultraviolet nanosecond lasers with wavelengths of 300-1000nm, pulse widths of 1-100ns, scanning speeds of 50-100mm / s, and power of 100-300mW.
[0039] The laser scanning path employs a three-dimensional spiral filling algorithm with a layer spacing of 100-1000 nm and a 60° rotation between adjacent layers. The medical dressing substrate 1 retains over 90% of its original mechanical properties after laser additive manufacturing.
[0040] In this invention, the micro-chamber monomers 21 are arranged in a honeycomb array, which can be either hexagonal or square. Their projected area is 100-2500μm², their depth is 100-5000nm, their density is 100-1000 per mm², and their cavity wall tilt angle is 70°-85°. This design facilitates laser processing while preserving the original mechanical properties of the substrate (elongation at break, mechanical strength, moisture permeability, etc.) and can load more drugs.
[0041] A connecting microchannel 22 is provided between adjacent microchamber monomers 21. The diameter of the connecting microchannel 22 is 1-5μm. The connecting microchannel 22 allows the drug 3 loaded in each microchamber monomer 21 to communicate with each other, and the drug 3 is more evenly distributed in the nano-silver microchamber 2.
[0042] Drug 3 includes one or more of the following: antibacterial agents, growth factors, and hemostatic agents.
[0043] Antibacterial agent: selected from at least one of the following antibacterial agents: broad-spectrum antibiotics, quaternary ammonium compounds, aloe vera, honey, phage peptides, carbon quantum dots, and traditional Chinese medicine ingredients with antibacterial or bacteriostatic effects.
[0044] Growth factors: selected from at least one of epidermal growth factor (EGF), basic fibroblast growth factor (bFGF), and vascular endothelial growth factor (VEGF).
[0045] Hemostatic agent: selected from at least one of fibrin glue, Yunnan Baiyao and norepinephrine.
[0046] Preferably, the mass ratio of antibacterial agents, growth factors and hemostatic agents in the compound drug system is customized according to the needs of the clinical scenario.
[0047] This utility model of medical dressing is suitable for the treatment of infected wounds, burn wounds, surgical incisions, and the care of diabetic foot ulcers and pressure sores, so as to achieve multiple synergistic effects of wound moisture balance, bacterial killing, promoting vascular endothelial regeneration and hemostasis.
[0048] Drug dosages are compounded according to the needs of different clinical scenarios. For example, in the case of infected wounds, the ratio of antibacterial agent: growth factor: hemostatic agent = 2:1:1; growth promotion phase (late wound / recovery phase) = 1:2:1; hemostatic phase = 1:1:2.
[0049] Alternatively, in one embodiment, drug 3 can be loaded in three layers within the microcompartment monomer 21: the top layer is a hemostatic agent, the middle layer is an antibacterial agent, and the bottom layer is a growth factor. Over time, different types of drugs are released, thereby accelerating patient recovery.
[0050] The present invention will be further described below with reference to the embodiments.
[0051] Example 1 The femtosecond laser micro / nano fabrication process involves dropping a photocurable precursor solution containing polyvinylpyrrolidone (PEG)-modified silver nanoparticles (concentration 2-6 mg / mL) with a particle size of 10-100 nm onto the etching area. The laser focus is precisely aligned with the film surface using a 63× objective lens. A three-dimensional helical path etching is performed using a femtosecond laser with a wavelength of 100-1000 nm, a pulse width of 10-100 fs, a scanning speed of 1-10 mm / s, and a power of 10-100 mW. The interlayer spacing is set to 100-1000 nm, with adjacent layers rotated 60°, forming a hexagonal honeycomb microcavity array with a depth of 100-5000 nm and a density of 100-1000 particles / mm². Subsequently, after laser-induced curing, the uncured silver nanoparticle-PEG solution is removed by sequential rinsing with ethanol for 20 minutes and immersion in ultrapure water for 12 minutes. Subsequently, the aforementioned honeycomb-shaped silver nano-chambers were adhered to an adhesive medical-grade substrate and fixed onto a precision displacement platform. Finally, a composite drug solution containing 0.5% quaternary ammonium salt, 10 μg / mL bFGF, and 1% fibrin glue was incubated into the microchambers, and dried for 18 hours to form a porous drug-loaded structure (see...). Figure 2 The microcompartments were incubated with fluorescently labeled clindamycin using the method described above. Confocal microscopy was then used for observation and quantitative fluorescence analysis. The final analysis showed that the drug loading achieved by this process reached 1.8 mg / cm², and three-dimensional fluorescence imaging confirmed the uniform distribution of the drug within the microcompartments (see...). Figure 3 After soaking the patch in PBS solution for 72 hours, the drug loading capacity still reached 43% (see...). Figure 5 This precise and controllable laser processing method effectively avoids thermal damage.
[0052] The conventional laser micro / nano fabrication process involves using a 300-1000 nm ultraviolet nanosecond laser with a pulse width of 1-100 ns, a scanning speed of 50-100 mm / s, and a power of 100-300 mW to perform two-dimensional reciprocating scanning processing on a photocurable precursor solution containing polyvinylpyrrolidone (PEG)-modified silver nanoparticles (concentration 5-10 mg / mL) with a particle size of 20-200 nm. The line spacing is set to 5-20 μm, forming a square microcavity array with a depth of 1-50 μm and a density of 10-100 particles / mm². Other drug preparation and detection methods are the same as described above.
[0053] Example 2 The interval laser processing involves mounting a plasma-treated polyurethane film onto a temperature-controlled sample stage (25±1℃). Using the same laser parameters, a single-layer microcavity is first processed by scanning along the X-axis at a speed of 6 mm / s. After a 3-minute interval to allow complete thermal diffusion, the sample stage is rotated 60° to etch the next layer. This process is repeated three times to complete the construction of multi-layer microcavities. This interval scanning method allows the microcavity depth to be increased from 100 nm to 5000 nm in a single layer, while simultaneously creating gaps at specific layers, thus forming interconnected microchannels with diameters of 1-5 μm between the cavities (see...). Figure 2 b).
[0054] Example 3 The mechanical properties of polyurethane films before and after laser processing were tested using an INSTRON 5944 micro-force testing system. Strip specimens measuring 75 mm in length and 10 mm in width were prepared according to ISO 527-3 standards and equilibrated for 24 hours at 23±2℃ and 50±5% humidity before testing. A 500N load cell was used, and tests were conducted at a tensile rate of 50 mm / min, with six parallel samples per group. The test results showed that the average tensile strength of the unprocessed polyurethane film (PU-U) was 12.3±0.8 MPa, and the elongation at break was 420±25%. The average tensile strength of the laser-processed but drug-free sample (PU-U-AL) was 11.1±0.7 MPa and 398±22%, respectively; while the average tensile strength of the laser-processed and drug-loaded sample (PU-S-AL) was 10.8±0.6 MPa and 385±20%, respectively. This indicates that the laser micro / nano processing technology retained more than 90% of the original mechanical properties of the substrate (see [link to relevant documentation]). Figure 4 ).
[0055] Example 4 Moisture permeability testing was conducted according to GB / T 12704.1-2009 standard using a TSY-T3 moisture permeability meter. 10g of anhydrous calcium chloride desiccant was added to the permeability cup, and a circular sample (50±2μm thick) with a diameter of 35mm was sealed and fixed at the cup opening. The cup was then placed in a constant temperature and humidity chamber at 37±0.5℃ and 90±2% relative humidity. After 24 hours, the mass change was measured, and the calculated moisture permeability was: 320±15g / (m²·24h) for PU-U, 310±12g / (m²·24h) for PU-U-AL, and 295±10g / (m²·24h) for PU-S-AL. This confirms that the microcavity structure of laser processing has less than 8% influence on the moisture permeability of the polyurethane substrate (see [link to relevant documentation]). Figure 4 To further verify its performance in actual use, the samples were placed in a simulated wound environment (temperature 32℃, humidity 95%) for 7 consecutive days. The moisture permeability fluctuation range was within ±5%, demonstrating excellent stability.
[0056] Example 5 For the antibacterial experiment, clinically isolated Staphylococcus aureus (ATCC 25923) was used as the test strain. Mueller-Hinton agar medium (containing 2% NaCl) was prepared according to CLSI standards. The frozen bacterial strain was inoculated into TSB liquid medium and cultured at 37℃ with shaking at 200 rpm until the logarithmic growth phase (OD600=0.6). The bacterial concentration was adjusted to 1×10^8 CFU / mL with PBS. Sterile 1cm×1cm samples (PU-U, PU-U-AL, PU-S-AL) were sterilized with UV light for 15 minutes and then placed in the center of the inoculated agar plate. After incubation at 37℃ for 72 hours, the diameter of the inhibition zone was measured. The results showed that the inhibition zone diameter of the PU-S-AL group reached 12.3±0.8mm, significantly larger than that of the PU-U-AL group (5.2±0.6mm) (p<0.01) (see [link to relevant documentation]). Figure 6 ).
[0057] Example 6 A full-thickness skin defect infection model was established in SD rats (weight 200±20g). After anesthesia, a 1.5cm×1.5cm square wound was prepared on the back, and 50μL of Staphylococcus aureus bacterial solution (1×10^7 CFU) was instilled to establish infection. After applying the test samples (PU-U, PU-S-AL) to different groups, the wound condition was observed daily. Histopathological findings showed (…). Figure 7 In the PU-S-AL group, inflammatory cell infiltration was reduced by 60% compared with the control group, and the thickness of the newly formed epithelial layer increased by 2.3 times.
[0058] Drug loading experiments showed that the patch prepared by this process exhibited an inhibition zone diameter of 12.3 ± 0.8 mm against Staphylococcus aureus. In vitro release tests showed a drug release rate exceeding 80% within 72 hours, and the drug loading variation between different batches was less than 5%, demonstrating good process stability. Animal experiments further confirmed that the patch prepared using this interval processing method reduced local inflammatory cell infiltration by 60% and increased the thickness of the newly formed epithelial layer by 2.3 times 7 days post-surgery compared to the control group (see...). Figure 7 ).
[0059] Example 7 Platelet adhesion assay was performed using fresh anticoagulated whole blood from rats. Platelet-rich plasma was obtained by centrifugation at 1000 rpm for 10 minutes, and the platelet concentration was adjusted to 3 × 10^8 cells / mL. 1 cm × 1 cm samples (PU-U, PU-U-AL, PU-S-AL) were placed in 24-well plates, and 500 μL of PRP was added to each well. After incubation at 37°C for 1 hour, the plates were gently washed three times with PBS to remove unadhered platelets. The plates were fixed with 4% paraformaldehyde for 30 minutes, stained with CD41 antibody, and observed under a fluorescence microscope. The results showed that the platelet adhesion density in the PU-S-AL group was (1285 ± 156) cells / mm², significantly higher than that in the PU-U group (312 ± 45) cells / mm² (p < 0.001) (see [link to study].) Figure 8 ).
[0060] This invention successfully constructs a multifunctional medical dressing based on laser additive manufacturing technology. By precisely processing with a laser, a honeycomb-shaped micro-cavity array is constructed on the surface of medical substrates such as polyurethane, achieving efficient loading and synergistic release of antibacterial, growth-promoting, and hemostatic drugs.
[0061] The microstructure of the polyurethane film is shown below. Figure 2 As shown, its surface forms an array of hexagonal microcavities with a depth of 100-5000nm and a density of 100-1000 per mm², and the cavities are connected by microchannels with a diameter of 1-5μm.
[0062] The mechanical properties of this polyurethane film are shown below. Figure 4 As shown, the laser-processed material retains excellent mechanical properties, with a tensile strength of 10.8±0.6MPa, an elongation at break of 385±20%, and a Young's modulus of 8-12MPa.
[0063] The moisture permeability of the polyurethane film is shown below. Figure 4 As shown, its moisture permeability is 295±10g / (m²·24h), which is only 8% lower than that of the unprocessed sample.
[0064] The 3D micro-nano laser etching process uses femtosecond lasers with wavelengths of 100-1000nm and pulse widths of 10-100fs, a scanning speed of 1-10mm / s, and a power of 10-100mW.
[0065] Conventional laser additive manufacturing processes use ultraviolet nanosecond lasers with wavelengths of 300-1000nm, pulse widths of 1-100ns, scanning speeds of 50-100mm / s, and power of 100-300mW.
[0066] Laser additive manufacturing technology has significantly increased the drug loading capacity of polyurethane dressings. Figure 3 As shown, the drug loading achieved by this process is 1.8 mg / cm².
[0067] The polyurethane film exhibits good drug release properties (see [reference needed]). Figure 5 As shown, the drug load decreased by only 45% after 72 hours.
[0068] Results of in vitro antibacterial experiments are shown below Figure 6 As shown, the PU-S-AL group exhibited an inhibition zone diameter of 12.3±0.8 mm against Staphylococcus aureus, which was significantly better than the control group.
[0069] Animal experiment results are shown in Figure 7 As shown, 7 days after surgery, the PU-S-AL group showed a 60% reduction in inflammatory cell infiltration and a 2.3-fold increase in the thickness of the newly formed epithelial layer compared to the control group.
[0070] The results of the hemostatic performance test are shown in Figure 8 As shown, the platelet adhesion density in the PU-S-AL group reached (1285±156) cells / mm².
[0071] This invention uses traditional medical-grade dressings as the substrate and constructs a honeycomb-shaped array of nano-silver microcavities using laser etching technology. While retaining the original breathability and flexibility of the substrate, it achieves intelligent regulation of the wound microenvironment. This technology significantly enhances the drug loading capacity of the substrate; the composite drug system loaded in the microcavities can simultaneously exert a synergistic effect of broad-spectrum antibacterial activity, promoting tissue regeneration, and rapid hemostasis. This dressing can effectively prevent and treat wound infections and significantly accelerate the healing process.
[0072] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the protection scope of this invention.
Claims
1. A multifunctional medical dressing assisted by laser additive manufacturing technology, comprising a medical dressing substrate (1), characterized in that: It also includes a nano-silver microcavity (2) for loading the drug (3), the nano-silver microcavity (2) being bonded to the medical dressing substrate (1), the nano-silver microcavity (2) being made of nano-silver composite material by laser processing, and having multiple microcavity monomers (21) capable of containing the drug (3).
2. The multifunctional medical dressing according to claim 1, characterized in that: The micro-chamber units (21) are arranged in a honeycomb array.
3. The multifunctional medical dressing according to claim 1, characterized in that: The projected area of the microchamber unit (21) is 100-2500μm², the depth is 100-5000nm, the inclination angle of the cavity wall is 70°-85°, and the density is 100-1000 units / mm².
4. The multifunctional medical dressing according to claim 1, characterized in that: The microchamber unit (21) is either hexagonal or square.
5. The multifunctional medical dressing according to claim 1, characterized in that: A connecting microchannel (22) is provided between adjacent microchamber units (21), and the diameter of the connecting microchannel (22) is 1-5 μm.
6. The multifunctional medical dressing according to claim 1, characterized in that: The drug (3) is loaded in three layers in the microchamber monomer (21): the top layer is a hemostatic agent, the middle layer is an antibacterial agent, and the bottom layer is a growth factor.
7. The multifunctional medical dressing according to claim 1, characterized in that: The drug (3) is loaded into the nano-silver microcavity (2) by means of hydrogel filling.